OPTIMALISASI PENERAPAN REKAM MEDIS ELEKTRONIK DI RUMAH SAKIT JIWA PROF. HB. SAANIN PADANG - Wahyuni, Annisa (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
In the current digital era, health information management has undergone a significant transformation with the adoption of Electronic Medical Records (RME). Prof. Mental Hospital HB. Saanin Padang has started implementing RME using the SIMRS application, which is an integrated communication information technology system. The transition process to RME is required to be completed no later than 31 December 2023, in accordance with Minister of Health Regulation (Permenkes) Number 24 of 2022 concerning Medical Records. The aim of this activity is to improve the efficiency and quality of mental health services through optimizing the implementation of RME. The methods used in this activity are socialization, brainstorming, SWOT analysis, which involves observation to identify existing strengths, weaknesses, opportunities and threats. The results of the activities show that the implementation of RME still faces various obstacles, including the lack of integrated RME between outpatient and inpatient units, the process of switching from manual to electronic systems, as well as the availability of budget and infrastructure. Further discussion shows that several strategies can be implemented to overcome these obstacles, such as conducting initial trials, providing intensive training, and optimizing budget use. In conclusion, optimization in the implementation of RME is expected to bring positive changes in mental health management in Indonesia.